Hairy ears; Revisited - Daifullah Al Aboud (Our Dermatology Online, 2014)
Hair can grow in areas which are not usually hairy in human skin. The Online Mendelian Inheritance in Man (OMIM) (http:// www.ncbi.nlm.nih.gov/omimhave) some entries in this regards. These include ( %139600 - HAIRY ELBOWS, #605130 - HAIRY ELBOWS, SHORT STATURE, FACIAL DYSMORPHISM, AND DEVELOPMENTAL DELAY, 139630 - HAIRY NOSE TIP, 139500 - HAIRY EARS, and 425500 - HAIRY EARS, Y-LINKED). Hairy ears, (Fig. 1), are uncommon trait and it is rare to see a person with very long hair on the ears.